Zonação em costões rochosos abrigados do Atlântico subtropical: variação espacial das comunidades, efeitos do biofilme e da mortalidade diferencial de cracas - Siquitelli, Jaqueline Cristiane (Universidade Federal de São Carlos, 2015)
The zonation of rocky shores results from the action of physical and chemical factors and of biological interactions within the benthic assemblages, being a good model to investigate factors that structure biological communities. In the present study, the objective was to evaluate the processes influencing a particular zonation pattern in sheltered rocky shores of Southeastern Brazil. The intermediate and lower midlittoral in these environments is a zone mainly formed by bare rock, or biofilm, presenting only few individuals of the barnacle Tetraclita stalactifera or other filtering-feeding species, whereas the upper midlittoral is dominated by the barnacle Chthamalus bisinuatus. In this way, we first evaluated the variation in these communities at three spatial scales (within shores, between shores and between regions), to identify the extension of the pattern (Chapter 1). Then, we carried out two experiments to test the assumptions that 1) the pattern would be determined by biofilm action, which would be distinct in the two zones and thus influence barnacle recruitment differentially; 2) the pattern would be determined by higher barnacle mortality in the lower zone, probably caused by higher predation pressure in this zone (Chapter 2). Our results allowed us to conclude that the main source of variation in the communities studied was usually at small spatial scales, meaning that the structuring processes in these communities would also occur at small scale. Barnacle recruitment during the study was excessively low and not correlated with different heights on the midlittoral, whereas the biofilm was more abundant in the lower midlittoral. In this midlittoral zone, barnacles showed higher mortality than in the upper midlittoral, evidencing strong effects of differential mortality structuring the community, although few predators were sampled in the studied areas. Thus, the present study contributes to our understanding of structuring processes in subtropical sheltered rocky shores, generating a reference framework on the system studied and subsidizing studies on environmental impacts.
Keywords: Comunidades; Variação (Biologia); Recrutamento; Biofilme; Mortalidade; Variação espacial; Cracas; Recrutamento; Biofilme; Spatial variation; Barnacles; Recruitment; Biofilm; Differential mortality; CIENCIAS BIOLOGICAS::ECOLOGIA